A Recipe for the Use of ICT Tools in an Educational Institute - Margaret, R. E.; Uma, B.; Tejonidhi, M. R.; Neelakantappa, B. B. (Journal of Engineering Education Transformations, 2018)
Information and Communication Technology (ICT) has become an indispensable tool for teaching learning and for effective management and administration of an educational institute. Use of ICT tools in an educational institute reduces manual work and enhances timeliness, effectiveness and efficiency. This is also environment friendly by saving paper. This paper describes simple use of ICT tools at various levels in an educational institute. The methods explained are very simple incurring no extra cost other than availability of internet and provides guidance to make an immediate beginning to use them. The use cases of each method are described thus enabling the reader to know how and where they can be adopted. The experience of using these in our institute has been well appreciated and accepted by administrators and other faculty members.